Peran Pelaksanaan Pengelolaan Kelas SD Negeri Bigaran - Gita Royani, Eflina; Wijayanto, Sukma (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
From the above problems, the purpose of this study is to assist teachers in goodclassroom management, having comfortable classrooms, neat spatial arrangement and theuse of media in learning to achieve learning objectives. This research was conducted inBigaran State Elementary School. This study was designed using a qualitative researchtype with the hope of improving the student learning process. The data analysis used isinductive which is used as an understanding of the data obtained. The data that can becollected are in the form of words, pictures, and numbers. The subjects of this study werefourth grade students at SDN Bigaran and the object of the research was the applicationof classroom management at SDN Bigaran. The research carried out was observing theclassroom, where the sitting position was arranged in such a way, the cleanliness of theroom, the decorations in the classroom. The teacher asks students to paste the student'swork, there are pictures of heroes, pictures of Indonesian culture, maps in such a way thatthe classroom does not look boring to students. Based on the results of interviews withclassroom teachers, students found that some students were able to follow and adjustconditions to the classroom environment. That way it will be easy for teachers in classroommanagement settings so that it will support the realization of the learning objectives to beachieved.